DAMPAK PENGEMBANGAN KETERAMPILAN KEWIRAUSAHAAN TERHADAP PRAKTIK WIRAUSAHA PADA MAHASISWA AKUNTANSI MANAJERIAL DI POLITEKNIK NEGERI BATAM - Abdullah, Riki Yusup; Lawita, Nadia Fathurrahmi (Pusat P2M Politeknik Negeri Batam, 2024)
This study aims to determine the impact of entrepreneurship education on attitudes, perceived behavioral control, intentions, and entrepreneurial behavior of Managerial Accounting students at Batam State Polytechnic. This study uses the Planned Behavior theory and a quantitative approach with a questionnaire as a data collection instrument. The results showed that participation in entrepreneurship education has a significant effect on perceived behavioral control and entrepreneurial behavior, but not on entrepreneurial career attitudes and student intentions. In addition, perceived behavioral control mediates the effect of entrepreneurship education on intentions, and student intentions mediate the effect of entrepreneurship education on entrepreneurial behavior.